Sleep is more than rest for plasticity in the human cortex. Issue 3 (6th January 2021) - Nissen, Christoph; Piosczyk, Hannah; Holz, Johannes; Maier, Jonathan G; Frase, Lukas; Sterr, Annette; Riemann, Dieter; Feige, Bernd
Abstract: Sleep promotes adaptation of behavior and underlying neural plasticity in comparison to active wakefulness. However, the contribution of its two main characteristics, sleep-specific brain activity and reduced stimulus interference, remains unclear. We tested healthy humans on a texture discrimination task, a proxy for neural plasticity in primary visual cortex, in the morning and retested them in the afternoon after a period of daytime sleep, passive waking with maximally reduced interference, or active waking. Sleep restored performance in direct comparison to both passive and active waking, in which deterioration of performance across repeated within-day testing has been linked to synaptic saturation in the primary visual cortex. No difference between passive and active waking was observed. Control experiments indicated that deterioration across wakefulness was retinotopically specific to the trained visual field and not due to unspecific performance differences. The restorative effect of sleep correlated with time spent in NREM sleep and with electroencephalographic slow wave energy, which is thought to reflect renormalization of synaptic strength. The results indicate that sleep is more than a state of reduced stimulus interference, but that sleep-specific brain activity restores performance by actively refining cortical plasticity.